2016
DOI: 10.1039/c6cp03388a
|View full text |Cite
|
Sign up to set email alerts
|

Light stability tests of CH3NH3PbI3 perovskite solar cells using porous carbon counter electrodes

Abstract: The CHNHPbI perovskite solar cells have been fabricated using three-porous-layered electrodes as, 〈glass/F-doped tin oxide (FTO)/dense TiO/porous TiO-perovskite/porous ZrO-perovskite/porous carbon-perovskite〉 for light stability tests. Without encapsulation in air, the CHNHPbI perovskite solar cells maintained 80% of photoenergy conversion efficiency from the initial value up to 100 h under light irradiation (AM 1.5, 100 mW cm). Considering the color variation of the CHNHPbI perovskite layer, the significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Moreover, the perovskite has a strong contact with the porous carbon electrodes, which was confirmed by XRD and XPS. 43 Although the carbon electrodes were a porous layer, the composite of porous carbon and perovskite can block the penetration of moisture to the photovoltaic active parts of solar cells. (3) The group with Han utilized HOOC(CH 2 ) 4 NH 2 (5-aminovaleric acid: 5AVA) in order to improve the contact strength between the CH 3 NH 3 PbI 3 and TiO 2 surface, 41 which prohibit the cleavage of the interface, resulting in the elimination of moisture introduction into the cells.…”
mentioning
confidence: 99%
“…Moreover, the perovskite has a strong contact with the porous carbon electrodes, which was confirmed by XRD and XPS. 43 Although the carbon electrodes were a porous layer, the composite of porous carbon and perovskite can block the penetration of moisture to the photovoltaic active parts of solar cells. (3) The group with Han utilized HOOC(CH 2 ) 4 NH 2 (5-aminovaleric acid: 5AVA) in order to improve the contact strength between the CH 3 NH 3 PbI 3 and TiO 2 surface, 41 which prohibit the cleavage of the interface, resulting in the elimination of moisture introduction into the cells.…”
mentioning
confidence: 99%
“…The degradation is severe under 1 equivalent sun, as expected for MAPI C-PSCs [35], and hinders any speculations. However, at 0.5 equivalent sun, the devices are stable for over 160 h.…”
Section: Resultsmentioning
confidence: 83%
“…The cells were sealed under ambient conditions with a relatively high humidity of 70 %, so that residual humidity may be present in the porous carbon layer. It should be noted that PCE of perovskite solar cells can be stabilized with the utilization of porous carbon layer, which can work as a good sealing material itself . Magna et al .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that PCE of perovskite solar cells can be stabilized with the utilization of porous carbon layer, which can work as a good sealing material itself. [27] Magna et al reported the degradation of CH 3 NH 3 PbI 3 perovskite crystal under ambient humidity and the reversibility and recovery of the cubic to tetragonal phase transition under inert Ar and N 2 atmospheres. [30] In this work, the recovery of photovoltaic parameters after thermal stress ( Figure 2) is suggested the sufficient barrier using appropriate sealing (Figure 1a) against possible attack by moistures and induced species diffusion.…”
Section: Resultsmentioning
confidence: 99%